Respostas
respondido por:
1
[- 2 x ( - 3/2 )² - 4 ] : ( - 2 )² - 3/4 =
[ - 2 x (9/4 - 4 ] : 4 - 3/4 =
[ - 2 x ( 9 - 16/4 ] : 4 - 3/4 =
[ - 2 x ( - 7/4 ] : 4 - 3/4 =
[+ 14/4 ] : 4 - 3/4 =
14/4 : 4 - 3/4 =
14/4 . 1/4 - 3/4 =
14/4 - 3/4 =
11/4
[ - 2 x (9/4 - 4 ] : 4 - 3/4 =
[ - 2 x ( 9 - 16/4 ] : 4 - 3/4 =
[ - 2 x ( - 7/4 ] : 4 - 3/4 =
[+ 14/4 ] : 4 - 3/4 =
14/4 : 4 - 3/4 =
14/4 . 1/4 - 3/4 =
14/4 - 3/4 =
11/4
daisycastro:
De nada, disponha! :-))
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás